POTENSI EKONOMI PEMANFAATAN LAHAN PEKARANGAN DI DESA SUKAJADI KECAMATAN SADANANYA KABUPATEN CIAMIS - Kurniawati, Tiktiek; Puspitasari, Anisa; Amalia, Lidya Nur; Adnan, Bahana Aditya (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2023)
This research was conducted with the aim of knowing the economic potential of using yards in Sukajadi village, Sadananya District, Ciamis Regency and to find out the form of using yards and the amount of capital needed to use the yards and contributing to the use of yards in increasing economic income for the people in the village. Sukajadi, Sadananya District, Ciamis Regency. This study uses a descriptive method with a quantitative approach. Data collection techniques were carried out in 3 ways, namely field surveys, questionnaires, and documentation. The population consists of 341 household heads. The sampling technique used is a simple random sampling technique. The results of the study found that land use in the form of yard land use has the potential to increase income. So that it can help the family economy. As for the form of land use yards that can increase income can be in the form of land use yards in other forms of business such as (groceries business, workshops, and so on). Meanwhile, the amount of income received before utilizing the land was only less than IDR 500,000 up to IDR 1,000,000. However, after utilizing the yard owned, the income earned increased by around IDR 1,000,000 or even more every month.